PENGARUH LEVEL INOKULAN DAN LAMA INKUBASI OLEH Aspergillus niger TERHADAP KANDUNGAN NUTRISI PUTAK - M. A. Hilakore; . Suryahadi; IGK. Wiryawan; D. Mangunwijaya (Partner, 2008)
The experiment used fermentation technique. Aspergillus niger was employed in attempting to increase the quality of putak. The experiment was arranged factorially using Completely Randomized Design 4 x 3. Factor A consisted of 4 levels of inoculants: 0.5, 1.0, 1.5, and 2.0% (w/w), while factor B consisted of incubation duration, that is 2, 3 and 4 days. Variables assessed were crude protein, true protein, crude fiber and dry matter contents of putak. The result showed that the treatments were significantly (P<0.05) affected the variables assessed. In conclusion, the treatments was improved the quality of putak. Keywords: putak, Aspergillus niger.